2022
DOI: 10.3389/fped.2022.947876
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cystic biliary atresia and choledochal cysts

Abstract: ObjectiveCystic biliary atresia (CBA) is a rare and peculiar type of biliary atresia (BA) that is easily confused with infantile choledochal cysts (CCs). This study explored information for early CBA diagnosis and treatment.MethodThe authors retrospectively analyzed the clinical data of 32 children with hilar cysts from January 2013 to May 2021. According to the diagnosis, they were divided into the CBA (n = 12) and CC (n = 20) groups. Patient features, biochemical indexes, preoperative ultrasound characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Noia et al ( 24 ) showed that early aspiration of fetal ovarian cysts that exceed 4.0 cm in diameter associate with a good longitudinal prognosis, while Sanna et al observed that 33% of cases increased antenatally in size ( 5 ). As observed by us and as previously reported by others, these dynamic observations may provide valuable information for the prediction of clinical outcomes in this population ( 25 , 26 ). The predictive model affirms the need to combine ultrasound characteristics and gestational age at diagnosis for intra-abdominal cystic lesions to effectively predict fetal outcomes, and may be useful for improving future clinical management strategies.…”
Section: Discussionsupporting
confidence: 83%
“…Noia et al ( 24 ) showed that early aspiration of fetal ovarian cysts that exceed 4.0 cm in diameter associate with a good longitudinal prognosis, while Sanna et al observed that 33% of cases increased antenatally in size ( 5 ). As observed by us and as previously reported by others, these dynamic observations may provide valuable information for the prediction of clinical outcomes in this population ( 25 , 26 ). The predictive model affirms the need to combine ultrasound characteristics and gestational age at diagnosis for intra-abdominal cystic lesions to effectively predict fetal outcomes, and may be useful for improving future clinical management strategies.…”
Section: Discussionsupporting
confidence: 83%